Etos Kerja Dan Motivasi Kerja Sebagai Kunci Meningkatkan Kinerja Karyawan - Komang Trisna Sari Dewi (ARTHA SATYA DHARMA, 2021)
Lembaga Perkredita Daerah (LPD) is a traditional and cultural-based financial institution that grows and develops in the Province of Bali. LPD is a village-owned financial enterprise that carries out business activities in the village environment and village krama. The purpose of this study was to determine the role and work ethic and work motivation of the employees of the Regional Credit Institutions in Grokgak District. The number of samples in this study were 85 respondents who were employees of the Regional Credit Institutions in Grokgak District. The data analysis techniques used in this research are structural equation modeling based on variance and component based SEM with smartPLS 3.0 analysis tools. Based on the results of hypothesis testing, it shows that work ethic has a significant positive effect on work motivation. Second, work ethic has a significant positive effect on employee performance. Third, work motivation has a significant positive effect on employee performance.